Rekonstruksi Peran Ganda Perempuan dalam Keluarga Perspektif Feminisme Islam: Kritik terhadap Hukum Keluarga Islam - Naim, Amal Zainun; Yustafad, Yustafad; Muna, Nailal (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This article discusses the dual role of women in the family within the context of Islamic family law and the need for its reconstruction to achieve gender equality. The aim of this research is to analyze the challenges women face in performing dual roles, both in domestic and public spheres, and to explore how Islamic family law can be reformed to be more responsive to women's needs. The methodology employed in this study is a qualitative approach with document analysis and literature review from various legal sources and Islamic feminist theories. The main discussion focuses on gender inequality in Islamic family law, the analysis of women’s roles in the workforce, and critiques of the patriarchal structure in conventional Islamic family law. The findings indicate that current Islamic family law still prioritizes women’s domestic roles, while their economic contributions are often overlooked. A reconstruction of Islamic family law based on maqashid sharia and gender equality principles is necessary to ensure that women can perform their dual roles without facing legal discrimination.